Experimental and Numerical Modeling of the Stress Rupture Behavior of Nickel-Based Single Crystal Superalloys Subject to Multi-Row Film Cooling Holes - Xu, Yuanming; Sun, Weikang; Dai, Wei; Hu, Chunyan; Liu, Xinling; Zhang, Weifang (Metals (Basel ), 2017)
The stress rupture behavior of nickel-base single crystal superalloys is a primary issue facing aero-engine design, which has been studied for more than 40 years. To a large degree, it is the existence of film cooling holes with the introduction of air cooling techniques that adds the extra challenge to the problem. Using both experimental and numerical methods, we explore here the stress rupture behavior of nickel base single crystal plate specimens subject to multi-row film cooling holes. As the numerical simulation part, finite element analysis using Abaqus was performed. Numerical results reveal that the existence of film-holes causes stress concentration and transforms local stress from uniaxial to multi-axial. For the stress distribution of different types of specimens, we defined a stress multiaxiality factor to quantitatively characterize the degree of the stress complexity and examined its effect on the rupture behaviors of the specimens along with the true stress concentration factor. The test was also carried out and results indicated that the creep rupture lives of one- and two-row specimens turn out to be longer than those of non-hole specimen. However, the three- and four-row configuration showed the opposite trend. Among the geometric parameters of film-hole configuration, film-hole row spacing is a predominant one influencing the creep rupture properties. Numerical results agree well with the fracture positions and shapes of specimens.